Additive manufacturing of advanced ceramic materials. (February 2021) - Lakhdar, Y.; Tuck, C.; Binner, J.; Terry, A.; Goodridge, R.
Abstract: Additive manufacturing (AM) has the potential to disrupt the ceramic industry by offering new opportunities to manufacture advanced ceramic components without the need for expensive tooling, thereby reducing production costs and lead times and increasing design freedom. Whilst the development and implementation of AM technologies in the ceramic industry has been slower than in the polymer and metal industries, there is now considerable interest in developing AM processes capable of producing defect-free, fully dense ceramic components. A large variety of AM technologies can be used to shape ceramics, but variable results have been obtained so far. Selecting the correct AM process for a given application not only depends on the requirements in terms of density, surface finish, size and geometrical complexity of the part, but also on the nature of the particular ceramic to be processed. This paper provides a detailed review of the current state-of-the-art in AM of advanced ceramics through a systematic evaluation of the capabilities of each AM technology, with an emphasis on reported results in terms of final density, surface finish and mechanical properties. An in-depth analysis of the opportunities, issues, advantages and limitations arising when processing advanced ceramics with each AM technology is also provided.